Republic of Honduras : Tegucigalpa Municipality PEFA - World Bank; PPIAF (World Bank, Washington, DC, 2013)
This Public Expenditure and Financial Accountability (PEFA) assessment of the public finance management (PFM) systems of the Municipality of the Central District of Honduras (AMDC) was prepared by a World Bank team, working closely together with the AMDC. The study is based on the Public Financial Management Performance Measurement Framework developed by the PEFA program. It incorporates the set of 28 indicators and 69 dimensions covering the entire budget cycle, drawing on international good practices for: (i) budget credibility; (ii) comprehensiveness and transparency; (iii) budget planning; (iv) predictability and control in budget execution; (v) accounting and reporting; and (vi) external scrutiny and audit. This assessment analyzes the performance of the Municipality of the AMDC PFM systems in terms of 28 high level performance indicators (PI) grouped into six core dimensions. International best practice standards are used as benchmarks for evaluating performance. The assessment provides a baseline against which PFM system performance can be assessed in future years; improved performance is reflected in higher ratings for the PIs. The PEFA assessment also may be used to help determine whether PFM reform strategies and action plans need to be adjusted.